Impact of kangaroo mother care on phototherapy duration and hospital stay in term neonates with neonatal jaundice: a cross-sectional study from South India - Pasha, Touheer; R., Afraneha; T., Hariharasudhan; Ramesh, Shanthi (International Journal of Research in Medical Sciences, 2025)
Background: Neonatal jaundice affects about 60% of term and 80% of preterm infants, primarily due to immature bilirubin metabolism. Phototherapy is the standard treatment, but prolonged exposure can cause complications such as dehydration, hypocalcemia, and disrupted maternal-infant bonding. Kangaroo mother care (KMC), involving skin-to-skin contact, has emerged as a supportive intervention that may enhance bilirubin excretion and reduce phototherapy duration. Objective was to assess the effect of KMC on phototherapy duration and hospital stay in term neonates with hyperbilirubinemia. Methods: A cross-sectional observational study was conducted from July 2023 to August 2024 at Sree Balaji Medical College and Hospital. A total of 120 term neonates (gestational age 37-42 weeks, birth weight >2500 gm) with jaundice requiring phototherapy were enrolled. Exclusion criteria included preterm birth, low birth weight, early-onset jaundice, hemolytic disease, or congenital anomalies. Infants were divided into two groups: group A (phototherapy only) and group B (phototherapy + KMC). Data were analyzed using SPSS v27. Results: The mean phototherapy duration was significantly lower in the KMC group (46.22±2.56 hours) than in the phototherapy-only group (65.13±6.88 hours) (p=0.02). Hospital stays were also significantly shorter in the KMC group (p<0.05). No adverse events related to KMC were reported. Higher gestational age and maternal education were associated with better outcomes. Conclusions: KMC is a safe, effective adjunct to phototherapy, reducing treatment duration and hospital stay while supporting mother-infant bonding.